The Impact of Government Expenditure and Labor Force on Regional Economic Growth: Evidence from Kendari, Indonesia - Lestari, Putri Ayu (Yayasan Sinergi Kawula Muda, 2025)
This study investigates the influence of government expenditure and labor force on economic growth in Kendari City, Indonesia, during the post COVID 19 recovery period from 2021 to 2023. Grounded in Keynesian economic theory, the research aims to assess whether public fiscal interventions and workforce dynamics significantly contribute to local economic performance in an emerging urban economy. A quantitative, non experimental approach was employed using multiple linear regression on secondary data obtained from official statistics. The findings reveal that both government expenditure and labor force have a positive but statistically insignificant relationship with economic growth. The R squared value of 0.318 indicates a moderate explanatory power, with the majority of economic variation left unexplained by the model. The insignificance may stem from model limitations, such as omitted variables and short time horizons, or structural issues in budget allocation and labor market efficiency. These results suggest that while public spending and labor inputs are directionally aligned with growth, their impacts may depend on contextual variables like institutional capacity and sectoral targeting. The study contributes to regional economic literature by offering empirical evidence from a mid sized Indonesian city, underlining the importance of coordinated fiscal and labor strategies. Future studies should incorporate longer term data and additional explanatory variables to capture the complex dynamics of local development.